Management morbidity and its impacts for women's life (Research, Society and Development, 2022)
Objective: To describe the impacts caused by gestational morbidities for women in their entire life context. Method: Exploratory study with a qualitative approach, carried out with 20 women hospitalized in the public maternity hospital, from September to October 2018, through an interview guided by a semi-structured script. The data were analyzed following Bardin's content analysis technique, the discussion had the Theory of the achievement of the maternal role as a methodological framework. The research was sent to the Research Ethics Committee of the Federal University of Alagoas, through Plataforma Brasil, for consideration, and approval was obtained under Nº. 87702318.8.0000.5013. Results: After analyzing the information obtained, the participants were characterized in sociodemographic and gynecological-obstetric data, and the thematic unit was selected: Impacts of the discovery of morbidity in the face of the gestational process and its subcategories: physical, financial, family impact, sexual and psychological. Conclusion: It was found that there are a series of physical, financial, family, sexual and psychological impacts that become part of women's lives after the discovery of gestational morbidity, and that to overcome them, it is necessary to give voice to these women, since this will allow them to apprehend and understand, from their peculiar experiences, the experience of medical and non-medical events to which they are exposed and which can generate vulnerabilities which must be considered.